Circadian and Metabolic Perspectives in the Role Played by NADPH in Cancer - Méndez, Isabel; Díaz-Muñoz, Mauricio (Frontiers in Endocrinology, 2018)
Physiological activity in healthy conditions requires a coordinated interaction between the molecular circadian clock and the network of biochemical pathways. An important metabolic parameter in the interface between these two entities is the redox state. Among the redox coenzymes that regulate the fluxes of enzymatic reactions is the NADP+/NADPH pair. Indeed, the main biosynthetic pathways need NADPH to serve as an electron donor for cellular anabolic transformations. The existence of a metabolic circadian clock is well established, and it was first identified in mammalian red blood cells. The metabolic circadian clock is independent of transcriptional activity and is sustained by the enzymatic complex peroxiredoxin/thioredoxin/NADPH. This complex shows 24-h redox fluctuations metabolizing H2O2 in a variety of tissues and species (fungi, insects, and mammals). Although this NADPH-sensitive metabolic clock is autonomous in erythrocytes that lack a nucleus, it functions in concert with the transcriptional circadian clock in other cell types to accomplish the task of timing cellular physiology. During carcinogenesis, circadian alterations influence cell cycle onset and promote tumoral growth. These alterations also deregulate cellular energetics through a process known as aerobic glycolysis, or the Warburg effect. The Warburg effect is a typical response of cancer cells in which the metabolism turns into glycolysis even in the presence of functional mitochondria. This alteration has been interpreted as a cellular strategy to increase biomass during cancer, and one of its main factors is the availability of NADPH. This minireview explores the potential role of NADPH as a circadian and cancer-promoting metabolite.